Przestępstwo stalkingu w regulacji kodeksu karnego: The crime of stalking in the regulation of the Criminal Code - Chamernik, Jarosław (Management and Administration Journal, 2021)
One of the special provisions of Part of the Criminal Code the offense of stalking is penalized by Law in art. 190a § 1. This provision was introduced by Law on the 25th February 2011 to amend the Criminal Code Act, announced on April 5th, 2011, which entered into force in June 2011. Stalking is defined as the persistent harassment or inducing circumstances justifiable to a sense of threat or significant invasion of privacy of another person or persons close to it. This article attempts to present conditions for the legal regulation of the crime of stalking in Poland and selected European countries.